(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2009)
Mild and transient hearing deficiency is not very uncommon after anaesthesia which improves before patient is fully aware of the problem. But complete prolong bilateral hearing loss after spinal anaesthesia is extremely rare complication, which falls in the category of sudden sensorineural hearing loss (SSNHL). The diagnosis and management of SSNHL is still controversial. doi: 10.3329/jafmc.v5i1.2854 JAFMC Bangladesh. Vol 5, No 1 (June) 2009 pp.53-55